2020
DOI: 10.1038/s41467-019-13990-w
|View full text |Cite
|
Sign up to set email alerts
|

Identification of distinct maturation steps involved in human 40S ribosomal subunit biosynthesis

Abstract: Technical problems intrinsic to the purification of preribosome intermediates have limited our understanding of ribosome biosynthesis in humans. Addressing this issue is important given the implication of this biological process in human disease. Here we report a preribosome purification and tagging strategy that overcomes some of the existing technical difficulties. Using these tools, we find that the pre-40S precursors go through two distinct maturation phases inside the nucleolus and follow a regulatory ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 52 publications
0
29
0
1
Order By: Relevance
“…To delineate the molecular mechanism at the origin of this phenotype, we analyzed pre-rRNA processing in RIOK2 WT Pre-40S particles containing the 18S-E pre-rRNA are generated in the nucleolus [64]. They undergo maturation steps in the nucleoplasm before being exported to the cytoplasm, where final maturation events lead to the production of the mature 18S rRNA of the 40S subunit [4].…”
Section: Riok2 Phosphorylation At Ser483 Is Required For Efficient Maturation Of Pre-40s Particlesmentioning
confidence: 99%
See 1 more Smart Citation
“…To delineate the molecular mechanism at the origin of this phenotype, we analyzed pre-rRNA processing in RIOK2 WT Pre-40S particles containing the 18S-E pre-rRNA are generated in the nucleolus [64]. They undergo maturation steps in the nucleoplasm before being exported to the cytoplasm, where final maturation events lead to the production of the mature 18S rRNA of the 40S subunit [4].…”
Section: Riok2 Phosphorylation At Ser483 Is Required For Efficient Maturation Of Pre-40s Particlesmentioning
confidence: 99%
“… (A) Schematic representation of pre-rRNA processing in human cells, adapted from [ 1 ] with precursor subcellular localization from [ 64 ]. Position of the probes (ITS1 and ITS2) used in Northern blot (NB) experiments to detect the pre-rRNAs are indicated.…”
Section: Supporting Informationmentioning
confidence: 99%
“…Very recently, we observed that the cytoplasmic PARN can locate on the endoplasmic reticulum (ER) via its CTD and shuttle between the cytosol and ER surface (Duan et al, 2020). Consistent with its multiple cellular locations, PARN not only regulates mRNA decay in the nucleus and cytoplasm, but also plays a crucial role in the biogenesis of various noncoding RNAs (ncRNAs) including microRNA (miRNAs) (Shukla, Bjerke, Muhlrad, Yi, & Parker, 2019), small nuclear RNAs (Berndt et al, 2012; Duan et al, 2019), telomere RNAs (Dhanraj et al, 2015; Moon et al, 2015), ribosomal RNAs (Benyelles et al, 2019; Ishikawa et al, 2017; Montellese et al, 2017; Nieto et al, 2020), and Y RNA (Shukla & Parker, 2017).…”
Section: Parn In Ddr and Genomic Stabilitymentioning
confidence: 99%
“…Besides miRNA, PARN also acts as a 3′‐end trimmer of snoRNAs (Berndt et al, 2012; Dhanraj et al, 2015; Duan et al, 2019; Son, Park, & Kim, 2018), telomere RNA (Benyelles et al, 2019; Boyraz et al, 2016; Deng et al, 2019; Dhanraj et al, 2015; Dodson et al, 2019; Mason & Bessler, 2015; Moon et al, 2015; Nguyen et al, 2015; Roake et al, 2019; Shukla, Schmidt, Goldfarb, Cech, & Parker, 2016; Stuart et al, 2015; Tummala et al, 2015), rRNA (Benyelles et al, 2019; Ishikawa et al, 2017; Montellese et al, 2017; Nieto et al, 2020), and Y RNA (Shukla & Parker, 2017). It is worth noting that a PARN homologue, PARN‐like domain‐containing 1 (PNLDC1) contributes to piRNA biogenesis in silkworms, Caenorhabditis elegans , and mammalians (Ding et al, 2017; Izumi et al, 2016; Tang, Tu, Lee, Weng, & Mello, 2016).…”
Section: Parn In Ddr and Genomic Stabilitymentioning
confidence: 99%
“…In recent years, numerous yeast proteins have been discovered as RBFs (e.g., Fujiyama-Nakamura et al, 2009 ; van Tran et al, 2019 ) whose presence in the archaea has not been tested in a comprehensive screen, thus far. Moreover, structure- and mass spectrometry-based approaches have shed light on the order of selected events during the assembly process and the identity of the participating proteins (see for example, Wu et al, 2016 ; Barandun et al, 2017 ; Kater et al, 2017 ; Sanghai et al, 2018 ; Klingauf-Nerurkar et al, 2020 ; Liang et al, 2020 ; Nieto et al, 2020 ). This resource, which provides an excellent basis for identifying functional sub-networks shared between eukaryotes and archaea, is largely untapped.…”
Section: Introductionmentioning
confidence: 99%